Design and characterization of mid-infrared Ge-on-Si resonant devices for sensing applications - Shu, Zhaolin (Nanyang Technological University, 2023)
Integrated optics have been studied for numerous applications including interconnect, biochemical sensing, and telecommunication. Owing to molecular vibration in the mid-infrared (MIR), there has been growing interest to realize on-chip devices for compact IR spectroscopy. Furthermore, realizing these on-chip MIR devices with CMOS-compatible processes and materials (Si, Ge) could lead to cheaper and miniaturized IR spectroscopic devices. This project will explore on-chip MIR optical devices based on germanium-on-silicon material platform for sensing application. The devices considered in this project include waveguides, grating coupler, directional couplers, mode splitter, and multi-mode interferometer. The project will cover various aspects from optical design and simulation to device testing and measurement. Through this project, the prospective reader will gain understanding of optical device concept including device design and optimization, as well as data processing.